2006
DOI: 10.1097/01.iae.0000244285.79004.e6
|View full text |Cite
|
Sign up to set email alerts
|

Zone I Retinopathy of Prematurity

Abstract: Atypical clinical features can be observed in zone I ROP. A posterior localization of the disease carries a worse prognosis after laser photocoagulation. Surgical intervention can effectively reattach the retina in a significant number of zone I ROP-related retinal detachments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 19 publications
1
46
0
Order By: Relevance
“…These recurrence rates are much higher than what we report in the present study even though the patient characteristics of our study and the BEAT-ROP study are similar. 25 While a few studies have reported a high recurrence rate (21%–78%) in eyes with Zone I ROP eyes treated with PRP, 2931 , these studies treated eyes with threshold ROP, which is associated with a higher recurrence rate than eyes with Type 1 ROP. 28 …”
Section: Discussionmentioning
confidence: 99%
“…These recurrence rates are much higher than what we report in the present study even though the patient characteristics of our study and the BEAT-ROP study are similar. 25 While a few studies have reported a high recurrence rate (21%–78%) in eyes with Zone I ROP eyes treated with PRP, 2931 , these studies treated eyes with threshold ROP, which is associated with a higher recurrence rate than eyes with Type 1 ROP. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Cryo-ablation was successful in 75 % of the cases in the CRYO-ROP Study. After the cryo era, even with high success rates of up to 98 % depending upon the severity of the disease, laser was not effective, particularly in zone I and aggressive posterior ROP (APROP) cases [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Most cases of APROP occurred in ultra-premature infants with a gestational age <26 weeks and birth weights <750 g [5-7,15]. However, all of the infants in this study had gestational ages >27 weeks and birth weights >1,000 g. Therefore, these findings suggest that APROP can occur in the absence of APROP risk factors, such as extremely low gestational age and very low birth weight [5-7].…”
Section: Discussionmentioning
confidence: 78%